Soldering tin alloy for packaging high-strength heat-conducting semiconductor and preparation method of soldering tin alloy
By adding copper-nickel-graphene intermediate alloy and trace phosphorus and germanium to the solder alloy, the hardness, wear resistance and thermal conductivity of the solder alloy are improved, and the problem of low stability and heat dissipation performance of lead-free solder materials at high temperatures is solved, and is suitable for packaging of high-performance electronic equipment.
Patent Information
- Application Number
- CN202411868822.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-18
AI Technical Summary
Existing lead-free solder materials have poor stability and low heat dissipation performance at high temperatures, making it difficult to meet the needs of high-frequency and high-speed signal transmission and heat dissipation of high-power devices.
Using solder alloys containing tin, copper, silver, germanium, phosphorus and copper-nickel-graphene intermediate alloys, the overall hardness, wear resistance and thermal conductivity of the material are improved through carefully designed component ratios and preparation processes.
It significantly improves the oxidation resistance, mechanical properties and thermal conductivity of solder alloys, solves the problem of insufficient stability and heat dissipation performance of traditional solder materials at high temperatures, and is suitable for high-density integrated circuit packaging of high-performance electronic devices.
Smart Images

Figure BDA0005195225350000081 
Figure BDA0005195225350000091
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of solder materials, and in particular to a solder alloy for high-strength thermal conductive semiconductor packaging and a preparation method thereof. Background Art
[0002] At present, the solder alloys widely used in the semiconductor packaging field mainly include Sn-Pb, Sn-Ag-Cu and other systems, but with the increasingly stringent environmental protection requirements, lead-free solders have gradually become the mainstream. However, lead-free solders generally have problems such as high melting point, poor wettability, and poor mechanical properties. Especially when dealing with high-frequency and high-speed signal transmission and high-power device heat dissipation requirements, existing lead-free solder materials often cannot meet the dual requirements of high strength and good thermal conductivity.
[0003] Existing lead-free solder materials are prone to microcracks in high-temperature working environments, resulting in reduced reliability of the connection points; at the same time, the thermal conductivity coefficient is generally low and cannot effectively dissipate the heat generated by high-power consumption components, thus restricting the further improvement of the performance of electronic products. Summary of the invention
[0004] The purpose of this application is to provide a high-strength thermal conductive semiconductor packaging solder alloy and a preparation method thereof in view of the deficiencies of current technology. The high-strength thermal conductive semiconductor packaging solder alloy of this application has high oxidation resistance, low slag production rate, mechanical properties and thermal conductivity. By adding copper-nickel-graphene intermediate alloy, not only the overall hardness and wear resistance of the material are improved, but also the thermal conductivity is significantly enhanced. It is particularly suitable for packaging of high-density integrated circuits in high-performance electronic devices, and solves the problems of low stability and heat dissipation efficiency of traditional solder materials at high temperatures. Adding trace amounts of phosphorus and germanium has no obvious effect on the melting temperature of the solder alloy, but reduces the slag production and improves the oxidation resistance of the solder alloy. In addition, the preparation method of this application is simple, with high production efficiency and low cost.
[0005] In the first aspect, the present application provides a solder alloy for high-strength thermal conductive semiconductor packaging, adopting the following technical scheme: a solder alloy for high-strength thermal conductive semiconductor packaging, comprising the following preparation raw materials, measured by mass: 97-98 parts of tin, 0.4-0.6 parts of copper, 0.6-0.8 parts of silver, 0.008-0.011 parts of germanium, 0.01-0.018 parts of phosphorus, and 0.8-1.2 parts of copper-nickel-graphene intermediate alloy.
[0006] By adopting the above technical solution, the high-strength thermal conductive semiconductor packaging solder alloy contains multiple elements, each of which plays a unique role in the alloy: Tin: As the main component, tin provides good electrical conductivity and a low melting point, making it easy to melt and form a strong connection after cooling. Copper: A small amount of copper increases the hardness and wear resistance of the alloy, and also improves the thermal conductivity. Silver: The addition of silver further enhances the electrical conductivity and thermal conductivity of the alloy, while improving the corrosion resistance. Germanium: Although the content of germanium is extremely small, it helps to reduce the melting temperature of the solder alloy and improve its oxidation resistance. Phosphorus: A trace amount of phosphorus also helps to improve oxidation resistance and reduce the amount of slag produced during welding. Copper-nickel-graphene master alloy: This composite master alloy significantly improves the overall hardness, wear resistance and thermal conductivity of the solder alloy, and is particularly suitable for the packaging of high-density integrated circuits, solving the problem of insufficient stability and heat dissipation efficiency of traditional solder materials at high temperatures. High oxidation resistance: The addition of germanium and phosphorus effectively improves the oxidation resistance of the alloy. Low slag rate: A trace amount of germanium and phosphorus reduces the amount of slag produced during welding. Mechanical properties and thermal conductivity: Copper, silver and copper-nickel-graphene master alloys together improve the hardness, wear resistance and thermal conductivity of the alloy. Uniform dispersion: The preparation process of copper-nickel-graphene master alloy ensures the uniform dispersion of graphene, further optimizes the microstructure of the alloy and improves its overall performance. In short, this solder alloy achieves excellent mechanical properties, thermal conductivity and oxidation resistance through a carefully designed composition ratio and preparation process, making it very suitable for high-density integrated circuit packaging in high-performance electronic devices.
[0007] Preferably, the mass ratio of the germanium to the phosphorus is 1:1.5.
[0008] By adopting the above technical solution, the mass ratio of germanium to phosphorus is 1:1.5. This ratio is designed to reduce production costs while ensuring that the solder alloy has high oxidation resistance, low slag production rate, excellent mechanical properties and thermal conductivity. Germanium is a semiconductor element, and its addition can improve the thermal stability and oxidation resistance of the solder alloy. At the same time, germanium can also improve the electrical conductivity and thermal conductivity of the solder alloy, thereby improving its application performance in high-density integrated circuit packaging. Phosphorus is a non-metallic element, and its addition can reduce the melting point of the solder alloy, improve its fluidity and spreadability, and thus reduce the amount of slag production. In addition, phosphorus can also improve the corrosion resistance and oxidation resistance of the solder alloy. By setting the mass ratio of germanium to phosphorus to 1:1.5, the production cost can be reduced while ensuring that the solder alloy has excellent performance. At the same time, this ratio design can also enable germanium and phosphorus to form stable compounds in the solder alloy, thereby further improving the performance of the solder alloy.
[0009] Preferably, the copper-nickel-graphene master alloy comprises the following raw materials, measured by mass: 15 parts of graphene oxide, 850 parts of ethanol, 15.3 parts of nickel acetate, 60.2 parts of pure copper powder, 4 parts of dopamine and 150 parts of tris(hydroxymethyl)aminomethane hydrochloride solution with a pH of 7.0.
[0010] Preferably, the method for preparing the copper-nickel-graphene master alloy comprises the following steps: S41, mixing graphene oxide, dopamine and ethanol according to parts by mass to prepare a graphene oxide dispersion; S42. Add nickel acetate, pure copper powder and tris(hydroxymethyl)aminomethane hydrochloride) solution with a pH value of 7.0 to the graphene oxide dispersion according to their mass fractions, stir evenly, heat to 50-55°C to react for 5-8 hours, concentrate to dryness, and collect the solid phase; S43. Calcine the solid phase at 1170-1190°C in a reducing atmosphere for 3-4 hours, and cool to room temperature to obtain a copper-nickel-graphene intermediate alloy.
[0011] By adopting the above technical scheme, in the preparation process of copper-nickel-graphene master alloy, the surface of graphene oxide is rich in oxygen-containing functional groups, and dopamine is used to nitrogen-modify graphene oxide, and the nickel element and pure copper powder are fully dispersed through nitrogen-containing groups and oxygen-containing functional groups to obtain a master alloy with smaller particle size and more uniform distribution; thereby further improving the dispersibility of the above components in the final solder alloy, achieving uniform dispersion of graphene, more stable structure, and more refined grains, and the prepared solder alloy presents excellent mechanical properties and heat dissipation performance. By adding copper-nickel-graphene master alloy, the overall hardness and wear resistance of solder alloy can be significantly improved. This is particularly important for the packaging of high-density integrated circuits in high-performance electronic devices, because in this environment, the material needs to have higher mechanical strength and wear resistance. As a material with high thermal conductivity, the addition of graphene can significantly enhance the thermal conductivity of solder alloy. This is of great significance for solving the problem of low heat dissipation efficiency of traditional solder materials at high temperatures, and helps to improve the stability and reliability of electronic equipment. Through the rich oxygen-containing functional groups on the surface of graphene oxide and the nitrogen modification of dopamine, the nickel element and pure copper powder can be fully dispersed, thereby obtaining an intermediate alloy with smaller particle size and more uniform distribution. This helps to further improve the dispersion of graphene in the final solder alloy and avoid the occurrence of agglomeration. Due to the uniform dispersion of graphene and the more stable structure, the solder alloy prepared exhibits excellent mechanical properties and heat dissipation properties. This is of great significance for improving the application performance of solder alloys.
[0012] Preferably, in step S43, the reducing gas is composed of argon and hydrogen, the volume percentage of argon in the reducing gas is 75-80%, and the remainder is hydrogen; the flow rate of the reducing gas is 4.5 L / min.
[0013] Preferably, the flake diameter of the graphene oxide is 0.5 μm-2 μm and the thickness is 0.8 nm-1.5 nm, and the purity of the pure copper powder is 99.99% and the particle size is 1-2 microns.
[0014] In a second aspect, the present application provides a method for preparing a solder alloy for high-strength thermal conductive semiconductor packaging, using the following technical solution: As a general technical concept, the present application also provides a method for preparing the above-mentioned high-strength thermal conductive solder alloy for semiconductor packaging, comprising the following steps: S71. Mix tin, copper, silver and germanium raw materials in proportion according to their weight fractions, preheat to 150-200° C., remove the surface oxide layer, and obtain a mixture; S72, under an argon atmosphere, feeding the mixed material into an induction furnace, heating it to fully melt it into a liquid state, and obtaining a molten alloy A; S73, sequentially adding phosphorus and a copper-nickel-graphene master alloy to the molten alloy A, heating it, stirring it, and fully melting it into a liquid state, and obtaining a molten alloy B; S74, casting the alloy melt B into a mold preheated to 100° C. to cool and form, then performing a first vacuum annealing heat treatment and a second vacuum annealing heat treatment, and finally rapidly cooling to room temperature to obtain a high-strength thermally conductive solder alloy for semiconductor packaging.
[0015] Preferably, in step S72, the heating is performed by heating to 360-400°C.
[0016] Preferably, in step S73, the heating is performed by heating to 440-450° C.; the stirring is performed at a speed of 400-500 rpm for 15-20 minutes.
[0017] Preferably, in step S74, the temperature of the first vacuum annealing heat treatment is 250°C-280°C, the time is 1h-2h, and the vacuum degree is 1kPa; the temperature of the second vacuum annealing heat treatment is 220°C-240°C, the time is 1h-2h, and the vacuum degree is 1kPa.
[0018] By adopting the above technical scheme, the first and second vacuum annealing heat treatments play a vital role in the preparation process of the solder alloy for high-strength thermal conductive semiconductor packaging, which is specifically reflected in the following aspects: 1. Promote grain recrystallization: The temperature of the first vacuum annealing heat treatment is relatively high, which helps to eliminate the residual stress generated by the alloy during the casting process and rapid cooling, and promotes the recrystallization of the grains. Through grain recrystallization, the grain density and uniformity of the solder can be improved, thereby improving the mechanical properties and corrosion resistance of the solder alloy. The temperature of the second vacuum annealing heat treatment is relatively low, which helps to further optimize the microstructure of the alloy and make the various elements more evenly distributed. This uniform element distribution can improve the composition uniformity and consistency of the solder alloy, thereby improving its welding performance, antioxidant performance and heat dissipation performance. 3. Improve mechanical properties and corrosion resistance: Through two vacuum annealing heat treatments at different temperatures, the microstructure and composition distribution of the solder alloy can be gradually adjusted and optimized, thereby improving its overall mechanical properties and corrosion resistance. This is particularly important for the packaging of high-density integrated circuits in high-performance electronic devices, because in this environment, the material needs to have higher mechanical strength and corrosion resistance. 4. Improve welding performance and oxidation resistance: The control of temperature and time parameters during vacuum annealing heat treatment can make the various elements in the alloy more evenly distributed, thereby improving the welding performance and oxidation resistance of the solder alloy. This is of great significance for improving the application performance of the solder alloy. 5. Improve production efficiency and reduce costs: Through a reasonable vacuum annealing process, while ensuring the performance of the solder alloy, the production cost can be reduced and the production efficiency can be improved. In summary, the first and second vacuum annealing heat treatments in step S74 play a vital role in the preparation process of the solder alloy for high-strength thermal conductive semiconductor packaging. They work together to improve the mechanical properties, corrosion resistance, welding performance and oxidation resistance of the solder alloy, thereby meeting the needs of high-density integrated circuit packaging in high-performance electronic devices.
[0019] In summary, the beneficial technical effects of this application are: 1. High oxidation resistance: By adding trace amounts of phosphorus and germanium, the oxidation resistance of the solder alloy has been significantly improved. Although these trace elements do not significantly change the melting temperature, they effectively reduce the generation of oxides during the welding process, thereby reducing the slag rate.
[0020] 2. Low slag production rate: Due to the addition of phosphorus and germanium, the oxide slag produced by the solder alloy during the melting and welding process is significantly reduced, which not only improves the welding quality and efficiency, but also reduces the complexity of subsequent cleaning work.
[0021] 3. Excellent mechanical properties: By adding copper-nickel-graphene master alloy, the overall hardness and wear resistance of the solder alloy are significantly enhanced. The master alloy achieves uniform dispersion of nickel elements and pure copper powder through nitrogen-modified graphene oxide, thereby improving the mechanical properties of the solder alloy.
[0022] 4. Excellent thermal conductivity: The introduction of graphene significantly improves the thermal conductivity of solder alloys, making them particularly suitable for the packaging of high-density integrated circuits in high-performance electronic devices, solving the problem of low heat dissipation efficiency of traditional solder materials in high-temperature environments.
[0023] 5. Efficient preparation process: The preparation method of the present application is simple and efficient, including the steps of preheating to remove the oxide layer, smelting, adding trace elements, casting and two vacuum annealing heat treatments. The whole process is easy to operate, with high production efficiency and low cost.
[0024] 6. Uniform microstructure: Through strict vacuum annealing heat treatment, the residual stress in the alloy is eliminated, the grains are refined and evenly distributed, which further improves the mechanical properties and corrosion resistance of the solder alloy. DETAILED DESCRIPTION
[0025] The embodiments of the present application will be described in detail below in conjunction with the examples, but those skilled in the art will understand that the following examples are only used to illustrate the present application and should not be considered to limit the scope of the present application. If the specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially, and the purity of all metals used is 99.9%, and the purity of phosphorus is 99.95%.
[0026] In the following examples and preparation examples, 1 part means 100 g.
[0027] Preparation Example 1 Preparation of copper-nickel-graphene master alloy A copper-nickel-graphene master alloy comprises the following raw materials, by mass: 15 parts of graphene oxide, 850 parts of ethanol, 15.3 parts of nickel acetate, 60.2 parts of pure copper powder, 4 parts of dopamine, and 150 parts of tris(hydroxymethyl)aminomethane hydrochloride solution with a pH of 7.0; the graphene oxide has a sheet diameter of 0.5 μm-2 μm and a thickness of 0.8 nm-1.5 nm; the pure copper powder has a purity of 99.99% and a particle size of 1-2 microns; The method for preparing a copper-nickel-graphene master alloy comprises the following steps: S41, mixing graphene oxide, dopamine and ethanol according to parts by mass to prepare a graphene oxide dispersion; S42, respectively adding nickel acetate, pure copper powder and tris(hydroxymethyl)aminomethane hydrochloride solution with a pH value of 7.0 to the graphene oxide dispersion according to their weight fractions, stirring evenly, heating to 50° C. to react for 8 hours, concentrating to dryness, and collecting the solid phase; S43. calcining the solid phase at 1170° C. for 4 hours in a reducing atmosphere, and cooling to room temperature to obtain a copper-nickel-graphene intermediate alloy; wherein the reducing gas is composed of argon and hydrogen, the volume percentage of argon in the reducing gas is 75%, and the remainder is hydrogen; the flow rate of the reducing gas is 4.5 L / min.
[0028] Preparation Example 2 Preparation of Copper-Nickel-Graphene Master Alloy A copper-nickel-graphene master alloy comprises the following raw materials, by mass: 15 parts of graphene oxide, 850 parts of ethanol, 15.3 parts of nickel acetate, 60.2 parts of pure copper powder, 4 parts of dopamine, and 150 parts of tris(hydroxymethyl)aminomethane hydrochloride solution with a pH of 7.0; the graphene oxide has a sheet diameter of 0.5 μm-2 μm and a thickness of 0.8 nm-1.5 nm; the pure copper powder has a purity of 99.99% and a particle size of 1-2 microns; The method for preparing a copper-nickel-graphene master alloy comprises the following steps: S41, mixing graphene oxide, dopamine and ethanol according to parts by mass to prepare a graphene oxide dispersion; S42, respectively adding nickel acetate, pure copper powder and tris(hydroxymethylaminomethane) hydrochloride solution with a pH value of 7.0 to the graphene oxide dispersion according to their weight fractions, stirring evenly, heating to 55° C. for reaction for 5 hours, concentrating to dryness, and collecting the solid phase; S43. calcining the solid phase at 1190° C. for 3 hours in a reducing atmosphere, and cooling to room temperature to obtain a copper-nickel-graphene intermediate alloy; wherein the reducing gas is composed of argon and hydrogen, the volume percentage of argon in the reducing gas is 80%, and the remainder is hydrogen; the flow rate of the reducing gas is 4.5 L / min.
[0029] Preparation Example 3 Preparation of Copper-Nickel-Graphene Master Alloy A copper-nickel-graphene master alloy comprises the following raw materials, by mass: 15 parts of graphene oxide, 850 parts of ethanol, 15.3 parts of nickel acetate, 60.2 parts of pure copper powder, 4 parts of dopamine, and 150 parts of tris(hydroxymethyl)aminomethane hydrochloride solution with a pH of 7.0; the graphene oxide has a sheet diameter of 0.5 μm-2 μm and a thickness of 0.8 nm-1.5 nm; the pure copper powder has a purity of 99.99% and a particle size of 1-2 microns; The method for preparing a copper-nickel-graphene master alloy comprises the following steps: S41, mixing graphene oxide, dopamine and ethanol according to parts by mass to prepare a graphene oxide dispersion; S42, respectively adding nickel acetate, pure copper powder and tris(hydroxymethyl)aminomethane hydrochloride solution with a pH value of 7.0 to the graphene oxide dispersion according to their weight fractions, stirring evenly, heating to 53° C. for reaction for 7 hours, concentrating to dryness, and collecting the solid phase; S43. calcining the solid phase at 1180° C. for 3.4 hours in a reducing atmosphere, and cooling to room temperature to obtain a copper-nickel-graphene intermediate alloy; wherein the reducing gas is composed of argon and hydrogen, the volume percentage of argon in the reducing gas is 78%, and the remainder is hydrogen; the flow rate of the reducing gas is 4.5 L / min.
[0030] Example 1 A high-strength thermally conductive solder alloy for semiconductor packaging, comprising the following raw materials by mass: 97 parts of tin, 0.4 parts of copper, 0.6 parts of silver, 0.008 parts of germanium, 0.01 parts of phosphorus, and 0.8 parts of copper-nickel-graphene master alloy; the copper-nickel-graphene master alloy is prepared by Preparation Example 1; The method for preparing the above-mentioned high-strength thermally conductive solder alloy for semiconductor packaging comprises the following steps: S71. Mix tin, copper, silver and germanium raw materials in proportion according to their weight fractions, preheat to 150° C., remove the surface oxide layer, and obtain a mixture; S72, under an argon atmosphere, feeding the mixed material into an induction furnace, heating it to 360° C. to fully melt it into a liquid state, and obtaining alloy melt A; S73, adding phosphorus and copper-nickel-graphene master alloy to the alloy melt A in sequence, raising the temperature to 440° C., stirring at a stirring speed of 400 rpm for 20 minutes to fully melt the alloy into a liquid state, and obtaining an alloy melt B; S74. Cast the alloy melt B into a mold preheated to 100°C and cool it into shape, then perform the first vacuum annealing heat treatment and the second vacuum annealing heat treatment, and finally quickly cool it to room temperature to obtain a high-strength thermal conductive solder alloy for semiconductor packaging; the first vacuum annealing heat treatment is performed at a temperature of 250°C, for 2 hours, and at a vacuum degree of 1 kPa; the second vacuum annealing heat treatment is performed at a temperature of 220°C, for 2 hours, and at a vacuum degree of 1 kPa.
[0031] Example 2 A high-strength thermally conductive solder alloy for semiconductor packaging, comprising the following raw materials by mass: 98 parts of tin, 0.6 parts of copper, 0.8 parts of silver, 0.011 parts of germanium, 0.018 parts of phosphorus, and 1.2 parts of copper-nickel-graphene master alloy; the copper-nickel-graphene master alloy is prepared by Preparation Example 2; The method for preparing the above-mentioned high-strength thermally conductive solder alloy for semiconductor packaging comprises the following steps: S71. Mix tin, copper, silver and germanium raw materials in proportion according to their weight fractions, preheat to 200° C., remove the surface oxide layer, and obtain a mixture; S72, under an argon atmosphere, feeding the mixed material into an induction furnace, heating it to 400° C. to fully melt it into a liquid state, and obtaining alloy melt A; S73, adding phosphorus and copper-nickel-graphene master alloy to the alloy melt A in sequence, raising the temperature to 450° C., stirring at a stirring speed of 500 rpm for 15 minutes to fully melt the alloy into a liquid state, and obtaining an alloy melt B; S74. Cast the alloy melt B into a mold preheated to 100°C and cool it into shape, then perform a first vacuum annealing heat treatment and a second vacuum annealing heat treatment, and finally quickly cool it to room temperature to obtain a high-strength thermal conductive solder alloy for semiconductor packaging; the first vacuum annealing heat treatment is performed at a temperature of 280°C, a time of 1 hour, and a vacuum degree of 1 kPa; the second vacuum annealing heat treatment is performed at a temperature of 240°C, a time of 1 hour, and a vacuum degree of 1 kPa.
[0032] Example 3 A high-strength thermally conductive solder alloy for semiconductor packaging, comprising the following raw materials by mass: 97.5 parts of tin, 0.5 parts of copper, 0.7 parts of silver, 0.009 parts of germanium, 0.012 parts of phosphorus, and 1 part of copper-nickel-graphene master alloy; the copper-nickel-graphene master alloy is prepared by Preparation Example 3; The method for preparing the above-mentioned high-strength thermally conductive solder alloy for semiconductor packaging comprises the following steps: S71. Mix tin, copper, silver and germanium raw materials in proportion according to their weight fractions, preheat to 180° C., remove the surface oxide layer, and obtain a mixture; S72, under an argon atmosphere, feeding the mixed material into an induction furnace, heating it to 390° C. to fully melt it into a liquid state, and obtaining alloy melt A; S73, adding phosphorus and copper-nickel-graphene master alloy to the alloy melt A in sequence, raising the temperature to 445° C., stirring at a stirring speed of 450 rpm for 17 minutes to fully melt the alloy into a liquid state, and obtaining an alloy melt B; S74. Cast the alloy melt B into a mold preheated to 100°C and cool it into shape, then perform a first vacuum annealing heat treatment and a second vacuum annealing heat treatment, and finally quickly cool it to room temperature to obtain a high-strength thermal conductive solder alloy for semiconductor packaging; the first vacuum annealing heat treatment is performed at a temperature of 270°C, a time of 1.4h, and a vacuum degree of 1kPa; the second vacuum annealing heat treatment is performed at a temperature of 230°C, a time of 1.4h, and a vacuum degree of 1kPa.
[0033] Example 4 The same as Example 3, except that 0.010 parts of germanium and 0.015 parts of phosphorus are used.
[0034] Comparative Example 1 The same as Example 4, except that there are 0 parts of germanium and 0 parts of phosphorus.
[0035] Comparative Example 2 The same as Example 4, except that an equal amount of mixed material (graphene oxide, pure nickel powder with a particle size of 2 microns and pure copper powder with a particle size of 1-2 microns mixed in a mass ratio of 15:3.7:60.2) is used instead of the copper-nickel-graphene intermediate alloy.
[0036] Comparative Example 3 The same as Example 4, except that, in step S74, there is only the first vacuum annealing heat treatment, and no second vacuum annealing heat treatment.
[0037] Comparative Example 4 The same as Example 4, except that, in step S74, there is no first vacuum annealing heat treatment, but only a second vacuum annealing heat treatment.
[0038] Performance Testing The high-strength thermally conductive solder alloy for semiconductor packaging prepared in Examples 1 to 4 and Comparative Examples 1 to 4 was sampled and made into welding rods for performance testing; Melting point: The melting temperature of the solder alloy was measured using a Diamondosc differential scanning calorimeter. The mass of the sample was about 10 mg, the test temperature range was 50-450°C, and the heating rate was 10°C / min. Wetting angle: measured using IPC-TM-6502.4.45 test method; Thermal conductivity: The thermal conductivity of the solder alloy was measured using a DynaCool thermal conductivity meter. The test temperature range was 37-97°C and the sample size was 2mm×2mm×8mm. Elongation test: According to GB / 11364-89 "Test method for solder spreading and filling properties", the greater the elongation, the better the solderability of the solder alloy for high-strength thermal conductive semiconductor packaging; Oxidation resistance: The oxidation resistance was tested by static oxidation method, the furnace temperature was 270℃, the mass was 500g, the slag was scraped every 60s, the slag was taken every 5min, each group was tested 3 times, and the average value of 3 times was taken; Corrosion resistance test: Determined using IPC-TM-6502.6.15 test method.
[0039] Table 1 Performance test Analyzing the data in Table 1, we can see that: 1) The high-strength thermally conductive solder alloy for semiconductor packaging prepared in Examples 1 to 4 has high oxidation resistance, low slag generation rate, mechanical properties and thermal conductivity.
[0040] 2) The performance comparison analysis of the high-strength thermal conductive semiconductor packaging solder alloy obtained in combination with Example 4, Example 3 and Comparative Example 1 shows that the mass ratio of germanium to phosphorus is 1:1.5. This ratio is designed to reduce production costs while ensuring that the solder alloy has high oxidation resistance, low slag production rate, excellent mechanical properties and thermal conductivity. By setting the mass ratio of germanium to phosphorus to 1:1.5, the production cost can be reduced while ensuring that the solder alloy has excellent performance. At the same time, this ratio design can also allow germanium and phosphorus to form a stable compound in the solder alloy, thereby further improving the performance of the solder alloy.
[0041] 3) The performance comparison analysis of the high-strength thermal conductive semiconductor packaging solder alloy obtained in combination with Example 4 and Comparative Example 2 shows that in the preparation process of the copper-nickel-graphene master alloy, the surface of graphene oxide is rich in oxygen-containing functional groups, and dopamine is used to nitrogen-modify graphene oxide, and the nickel element and pure copper powder are fully dispersed through nitrogen-containing groups and oxygen-containing functional groups to obtain a master alloy with a smaller particle size and more uniform distribution; thereby further improving the dispersibility of the above components in the final solder alloy, achieving uniform dispersion of graphene, a more stable structure, and more refined grains, and the prepared solder alloy exhibits excellent mechanical properties and heat dissipation performance. By adding the copper-nickel-graphene master alloy, the overall hardness and wear resistance of the solder alloy can be significantly improved. This is particularly important for the packaging of high-density integrated circuits in high-performance electronic devices, because in this environment, the material needs to have higher mechanical strength and wear resistance. As a material with high thermal conductivity, the addition of graphene can significantly enhance the thermal conductivity of the solder alloy. This is of great significance for solving the problem of low heat dissipation efficiency of traditional solder materials at high temperatures, and helps to improve the stability and reliability of electronic equipment. Through the rich oxygen-containing functional groups on the surface of graphene oxide and the nitrogen modification of dopamine, the nickel element and pure copper powder can be fully dispersed, thereby obtaining an intermediate alloy with smaller particle size and more uniform distribution. This helps to further improve the dispersibility of graphene in the final solder alloy and avoid the occurrence of agglomeration. Due to the uniform dispersion of graphene and the more stable structure, the solder alloy prepared exhibits excellent mechanical properties and heat dissipation properties. This is of great significance for improving the application performance of solder alloys.
[0042] 4) The performance comparison analysis of the high-strength thermal conductive semiconductor encapsulation solder alloy obtained in combination with Example 3 and Comparative Examples 3-4 shows that the first and second vacuum annealing heat treatments play a vital role in the preparation process of the high-strength thermal conductive semiconductor encapsulation solder alloy, which is specifically reflected in the following aspects: 1. Promote grain recrystallization: The temperature of the first vacuum annealing heat treatment is relatively high, which helps to eliminate the residual stress generated by the alloy during the casting process and rapid cooling, and promotes the recrystallization of the grains. Through grain recrystallization, the grain fineness and uniformity of the solder can be improved, thereby improving the mechanical properties and corrosion resistance of the solder alloy. The temperature of the second vacuum annealing heat treatment is relatively low, which helps to further optimize the microstructure of the alloy and make the various elements more evenly distributed. This uniform element distribution can improve the composition uniformity and consistency of the solder alloy, thereby improving its welding performance, antioxidant performance and heat dissipation performance. 3. Improve mechanical properties and corrosion resistance: Through two vacuum annealing heat treatments at different temperatures, the microstructure and composition distribution of the solder alloy can be gradually adjusted and optimized, thereby improving its overall mechanical properties and corrosion resistance. This is particularly important for the packaging of high-density integrated circuits in high-performance electronic devices, because in this environment, the material needs to have higher mechanical strength and corrosion resistance. 4. Improve welding performance and oxidation resistance: The control of temperature and time parameters during vacuum annealing heat treatment can make the various elements in the alloy more evenly distributed, thereby improving the welding performance and oxidation resistance of the solder alloy. This is of great significance for improving the application performance of the solder alloy. In summary, the first and second vacuum annealing heat treatments in step S74 play a vital role in the preparation process of the solder alloy for high-strength thermal conductive semiconductor packaging. They work together to improve the mechanical properties, corrosion resistance, welding performance and oxidation resistance of the solder alloy, thereby meeting the needs of high-density integrated circuit packaging in high-performance electronic devices.
[0043] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation modes of the present invention can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the scope of protection of the present application.
Claims
1. A high-strength thermally conductive solder alloy for semiconductor packaging, characterized in that: The preparation raw materials include the following by weight: 97-98 parts of tin, 0.4-0.6 parts of copper, 0.6-0.8 parts of silver, 0.008-0.011 parts of germanium, 0.01-0.018 parts of phosphorus, and 0.8-1.2 parts of copper-nickel-graphene intermediate alloy.
2. A high-strength thermally conductive solder alloy for semiconductor packaging according to claim 1, characterized in that: The mass ratio of the germanium to the phosphorus is 1:1.
5.
3. The high-strength thermally conductive solder alloy for semiconductor packaging according to claim 1, characterized in that: The copper-nickel-graphene master alloy comprises the following raw materials by weight: 15 parts of graphene oxide, 850 parts of ethanol, 15.3 parts of nickel acetate, 60.2 parts of pure copper powder, 4 parts of dopamine and 150 parts of tris(hydroxymethyl)aminomethane hydrochloride solution with a pH of 7.
0.
4. The high-strength thermally conductive solder alloy for semiconductor packaging according to claim 3, characterized in that: The method for preparing the copper-nickel-graphene master alloy comprises the following steps: S41, mixing graphene oxide, dopamine and ethanol according to parts by mass to prepare a graphene oxide dispersion; S42, respectively adding nickel acetate, pure copper powder and tris(hydroxymethyl)aminomethane hydrochloride solution with a pH value of 7.0 to the graphene oxide dispersion according to their weight fractions, stirring evenly, heating to 50-55° C. to react for 5-8 hours, concentrating to dryness, and collecting the solid phase; S43, calcining the solid phase at 1170-1190° C. for 3-4 hours in a reducing atmosphere, and cooling to room temperature to obtain a copper-nickel-graphene intermediate alloy.
5. The high-strength thermally conductive solder alloy for semiconductor packaging according to claim 4, characterized in that: In step S43, the reducing gas is composed of argon and hydrogen, the volume percentage of argon in the reducing gas is 75-80%, and the remainder is hydrogen; the flow rate of the reducing gas is 4.5 L / min.
6. The high-strength thermally conductive solder alloy for semiconductor packaging according to claim 3, characterized in that: The sheet diameter of the graphene oxide is 0.5 μm-2 μm and the thickness is 0.8 nm-1.5 nm. The purity of the pure copper powder is 99.99% and the particle size is 1-2 microns.
7. A method for preparing a high-strength thermally conductive solder alloy for semiconductor packaging according to any one of claims 1 to 6, characterized in that: The following steps are involved: S71. Mix tin, copper, silver and germanium raw materials in proportion according to their weight, preheat to 150-200° C., remove the surface oxide layer, and obtain a mixture; S72, under an argon atmosphere, feeding the mixed material into an induction furnace, heating it to fully melt it into a liquid state, and obtaining alloy melt A; S73, adding phosphorus and copper-nickel-graphene master alloy to the alloy melt A in sequence, heating and stirring to fully melt the alloy melt into a liquid state, to obtain alloy melt B; S74, casting the alloy melt B into a mold preheated to 100° C. to cool and form, then performing a first vacuum annealing heat treatment and a second vacuum annealing heat treatment, and finally rapidly cooling to room temperature to obtain a high-strength thermally conductive solder alloy for semiconductor packaging.
8. The method for preparing a high-strength thermally conductive solder alloy for semiconductor packaging according to claim 7, characterized in that: In step S72, the temperature is raised to 360-400°C.
9. The method for preparing a high-strength thermally conductive solder alloy for semiconductor packaging according to claim 7, characterized in that: In step S73, the heating is performed by heating to 440-450°C; the stirring is performed at a speed of 400-500 rpm for 15-20 minutes.
10. The method for preparing a solder alloy for high-strength thermal conductive semiconductor packaging according to claim 7, characterized in that: In step S74, the temperature of the first vacuum annealing heat treatment is 250°C-280°C, the time is 1h-2h, and the vacuum degree is 1kPa; the temperature of the second vacuum annealing heat treatment is 220°C-240°C, the time is 1h-2h, and the vacuum degree is 1kPa.
Citation Information
Patent Citations
High-performance lead-free solder for electronic industry
CN113770589A
Preparation and packaging method of graphene reinforced tin-based composite solder
CN114951947A
High-strength aluminum alloy and preparation method and application thereof
CN116855798A
High-ductility tin-silver-copper-nickel solder and preparation method thereof
CN117773407A
Weliding rod
KR1020170084566A